2009
DOI: 10.4162/nrp.2009.3.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and gender differences of beverage consumption in elementary school students

Abstract: The purpose of this study was to compare the beverage consumption by gender and season in elementary school children and to investigate the role of beverage consumption patterns on their daily nutrient intakes and BMIs. Beverage consumption and dietary energy intake in 160 elementary school students in the Gyeongnam area were measured by a beverage frequency and quantity questionnaire and three 24-hour dietary recalls during winter and summer. The number of drinking moments per month, the amounts of beverage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
3
1
Order By: Relevance
“…Accordingly, water, soft drinks and total beverage consumption were higher in the warm than the cold season, whereas alcohol and beverage total energy intake were higher in the cold season. These results are quite different from previous results in Korean school students that showed no differences between winter and summer on amounts of beverage per day and the daily energy intake from beverage consumption [ 52 ]. However, Korean girls, similarly to ours, also showed higher consumption of sweetened beverages in the warm season.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, water, soft drinks and total beverage consumption were higher in the warm than the cold season, whereas alcohol and beverage total energy intake were higher in the cold season. These results are quite different from previous results in Korean school students that showed no differences between winter and summer on amounts of beverage per day and the daily energy intake from beverage consumption [ 52 ]. However, Korean girls, similarly to ours, also showed higher consumption of sweetened beverages in the warm season.…”
Section: Discussioncontrasting
confidence: 99%
“…Milk was the most frequently consumed commercial beverage for total subjects in this study, which is consistent to the result on elementary school students, in which milk was the highest amount of beverage consumed among all beverages [ 25 ]. Frequent snacking and skipping meals as well as westernized type of breakfast have been associated with high consumption of beverages in previous studies done in adolescents [ 26 ], in which water was the most often chosen drink for meals primarily consisted of rice, while milk was the one with bread.…”
Section: Discussionsupporting
confidence: 90%
“…Although the results were not statistically significant, we observed higher consumption of sugar-sweetened beverages at higher temperatures in arid and temperate regions. Though evidence is limited, some studies have reported higher intake of sugar-sweetened beverages in the summer than in the winter ( 43 , 44 ), which suggests that the consumption of this type of beverages is higher as the temperature increases. We also observed that the consumption of high-energy ultra-processed foods, specifically cookies, pastries, and sweet bread, was higher at higher temperatures in tropical regions.…”
Section: Discussionmentioning
confidence: 99%